PENINGKATAN KEMAMPUAN KOGNITIF DALAM PEMBELAJARAN BERMAIN BALOK ANAK KELOMPOK A TK NEGERI KEPANJENKIDUL - KUSMIATI KUSMIATI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The purpose of this study is to describe the application of play and to describe the increase in cognitive abilities in group A children of TKN Kepanjenkidul I Blitar City. The lack or low cognitive ability of children in terms of playing with blocks in group A children at TKN Kepanjenkidul I Blitar City. This study used classroom action research which was carried out in 2 cycles, each cycle consisting of 2 meetings, each cycle consisting of planning, action, observation and reflection. The application of playing blocks can improve cognitive abilities seen from the first cycle of the first meeting the teacher's activity obtained 61.5% and the child's activity was 69.5% the child's attitude value 37.5% the child's knowledge value 31.25% the children's skill score 50% improved at the meeting 2. Meeting 2 teacher activities get 69.5%, children's activities 61.5% the value of the child's attitude 31.25% the value of the child's knowledge 31.25% the value of the child's skill 56.25% because it has not reached completeness then it is corrected in cycle 2. Results Cycle II, the first meeting of teacher activities, obtained 76.92% of children's activities, 69.23% of children's attitudes, 62.5% of children's knowledge, 68.75% of children's skills, 75% of children's skills. In the second meeting, teacher activities were 100%, children's activities were 92.3%, attitude values ??were 81.25%, knowledge values ??were 93.75%, and children's skills were 93.75%. The conclusion is that the application of playing blocks can increase teacher activity and children's activities as well as the cognitive abilities of group A TK Negeri Kepanjenkidul I, Kepanjenkidul District, Blitar City. ABSTRAKTujuan penelitian ini mendiskrisikan penerapan bermain dan mendiskripsikan peningkatan kemampuan kognitif pada anak kelompok A TKN Kepanjenkidul I Kota Blitar. Minimnya atau rendahnya kemampuan kognitif anak dalam hal bermain balok pada anak kelompok A di TKN Kepanjenkidul I Kota Blitar. Penelitian ini menggunakan penelitian tindakan kelas yang dilaksanakan 2 siklus masing-masing siklus terdiri 2 pertemuan setiap siklus terdiri dari perencanaan, tindakan, observasi dan refleksi. Penerapan bermain balok dapat meningkatkan kemampuan kognitif terlihat dari pada siklus I pertemuan pertama aktivitas guru memperoleh 61,5% dan aktivitas anak 69,5% nilai sikap anak 37,5% nilai pengetahuan anak 31,25% nilai ketrampilan anak 50% diperbaiki pada pertemuan 2. Pertemuan 2 aktivitas guru memperoleh 69,5%, aktivitas anak 61,5% nilai sikap anak 31,25% nilai pengetahuan anak 31,25% nilai ketrampilan anak 56,25% karena belum mencapai ketuntasan maka diperbaiki pada siklus 2. Hasil siklus II pertemuan pertama aktivitas guru memperoleh 76,92% aktifitas anak 69,23% nilai sikap anak 62,5%, nilai pengetahuan anak 68,75% nilai ketrampilan anak 75%. Pertemuan 2 aktivitas guru 100%, aktivitas anak 92,3% nilai sikap 81,25% nilai pengetahuan 93,75%, nilai ketrampilan anak 93,75%. Kesimpulan bahwa dengan penerapan bermain balok dapat mening katkan aktivitas guru dan aktivitas anak serta kemampuan kognitif kelompok A TK Negeri Kepanjenkidul I Kecamatan Kepanjenkidul Kota Blitar.